Eksplorasi Kepemimpinan dalam Meningkatkan Motivasi Karyawan dan Kinerja Toko: Studi Kasus Kepala Toko Alfamart Plosowahyu - Maitra Towifin; Darianto Darianto; Amanatul Khoiriyah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This study aims to explore in depth the role of leadership in fostering employee motivation and enhancing store performance among Alfamart store managers in Lamongan Regency. A qualitative research method employing a case study approach was used, enabling a contextual and comprehensive understanding of the phenomenon. Data were collected through observation, in-depth interviews, and document analysis involving store managers and employees actively engaged in store operations. The findings indicate that a participatory and communicative leadership style plays a significant role in boosting employee motivation. This is achieved through the expression of appreciation, the inclusion of employees in decision-making processes, and the practice of open and transparent communication. High levels of employee motivation positively impact store performance, particularly regarding the successful execution of operational tasks and the achievement of planned sales targets. However, the study also identified certain challenges such as miscommunication, time constraints, and interpersonal disagreements that can affect operational effectiveness. Consequently, adaptive and solution oriented leadership strategies are required. Overall, this study confirms the existence of a close relationship and significant mutual influence among leadership, employee motivation, and store performance.